A Matlab-Based Tool for Video Quality Evaluation without Reference - Zach, Ondrej; Slanina, Martin (Společnost pro radioelektronické inženýrství, 2014)
This paper deals with the design of a Matlab based tool for measuring video quality with no use of a reference sequence. The main goals are described and the tool and its features are shown. The paper begins with a description of the existing pixel-based no-reference quality metrics. Then, a novel algorithm for simple PSNR estimation of H.264/AVC coded videos is presented as an alternative. The algorithm was designed and tested using publicly available video database of H.264/AVC coded videos. Cross-validation was used to confirm the consistency of results.
Keywords: Quality assessment; GBIM; PSNR; MOS; image quality; H.264/AVC; quality metric